Recent advances in solar drying system: A review - M. A. S. M., Tarminzi; Amir, Abdul Razak; M. A. A., Azmi; Y. H., Ming; M. R. M., Akramin; N. M., Mohktar; A. F., Sharol (Penerbit Universiti Malaysia Pahang, 2021)
Research on solar dryer technology proliferates since it reduces the drying period while keeping nutritional values in the agricultural products. This paper presented a review of recent advances in the solar drying system. This review is composed of working principles and classifications of solar dryers. They were classified into two main elements: airflow modes, either passive or active, and the way heat is transferred: direct, indirect, mixed-mode, and hybrid. The hybrid system used several types of elements to supply additional heat in the drying system, as elaborated in this paper, such as the electrical heater, biomass, and photovoltaic system. The advantages and disadvantages of the solar dryer also being discussed in this paper